Analysis of factors affecting student Bidik Misi savings behavior - Amilia, Suri; Lindung Bulan, Tengku Putri; Rizal, Muhammad (Universitas Muhammadiyah Pontianak, 2018)
The objective of the research was to find out the financial literacy, socialization of parents, peers, and self-control influence of the saving behavior of bidik misi students on Fakultas Ekonomi - Universitas Samudra. The research type is quantitative descriptive that comes from primary data and secondary data. Data collection techniques conducted by distributing questionnaires with a Likert scale with the number of respondents as many as 201 people. Data analysis method using multiple linear regression, with multiple linear regression analysis equation in research are: Y = 7,672 + 0,201X1 + 0,403X2 + 0,049X3 + 0,387X4. The value of Adjusted R Square obtained by 0,328 or 32,8% indicates the ability of financial literacy variables, socialization of parents, peers, and self-control in explaining the saving behavior of 32,8%, while the remaining 67,2% is influenced by other factors not researched. Significant value for financial literacy is 0,009 < alpha 0,05, financial literacy variable has a significant effect of the saving behavior, and the hypothesis accepted. Significant value for the socialization of parents 0,000 < alpha 0,05, Variables of socialization of parents significantly influence the saving behavior. Thus the hypothesis accepted. Significant value for peers of 0,550 > alpha 0,05, Peer variables significantly influence the behavior saving. Thus the hypothesis is rejected. Significance value for self-control 0.000 < alpha 0,05, Self-control variable have a significant effect on the saving behavior, and the hypothesis accepted.